Discharge of contract and surrender under life insurance and family takaful: a comparative study - Yusuf Sani Abu Bakar,; Muhammad Anowar Zahid,; Ruzian Markon, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This is a doctrinal and comparative research between the traditional law and the syariah with regard to discharge of policies and surrender. The aim is to find similarities and dissimilarities between life insurance and family takaful vis-à-vis the issues. The issues are: Discharge of life policies/family takaful and this will cover discharge by Performance; Payment by Mistake; discharge by agreement, discharge by breach and cancellation. Moreover, the researcher explore surrender under life insurance and family takaful, which will deliberate on the concept and procedure for surrender. It has been found that both the traditional law and the syariah agree that a contract of life insurance and family takaful may be discharged by performance, by agreement, by breach, payment by mistake and cancellation. With regard to surrender, it has been found that both the Financial Services Act 2013 and the Islamic Financial Services Act 2013 allow it. It has been submitted that surrender is not against the syariah, since the purpose is to ensure good for the participants provided it is done in accordance with fair dealing. Moreover, both the traditional law and the syariah share the same view in the procedure for the surrender as it is required to be in a writing form.